Quantification of Ataxin-3 and Ataxin-7 aggregates formed in vivo in Drosophila reveals a threshold of aggregated polyglutamine proteins associated with cellular toxicity - Vinatier, Gérald; Corsi, Jean-Marc; Mignotte, Bernard; Gaumer, Sébastien (Biochemical and biophysical research communications, 2015)
Polyglutamine diseases are nine dominantly inherited neurodegenerative pathologies caused by the expansion of a polyglutamine domain in a protein responsible for the disease. This expansion leads to protein aggregation, inclusion formation and toxicity. Despite numerous studies focusing on the subject, whether soluble polyglutamine proteins are responsible for toxicity or not remains debated. To focus on this matter, we evaluated the level of soluble and insoluble truncated pathological Ataxin-3 in vivo in Drosophila, in presence or absence of two suppressors (i.e. Hsp70 and non-pathological Ataxin-3) and along aging. Suppressing truncated Ataxin-3-induced toxicity resulted in a lowered level of aggregated polyglutamine protein. Interestingly, aggregates accumulated as flies aged and reached a maximum level when cell death was detected. Our results were similar with two other pathological polyglutamine proteins, namely truncated Ataxin-7 and full-length Ataxin-3. Our data suggest that accumulation of insoluble aggregates beyond a critical threshold could be responsible for toxicity. [Display omitted] •The level of aggregated forms of polyQ proteins associates with toxicity.•Suppressors of polyQ protein-induced toxicity lower the level of cellular aggregates.•PolyQ protein aggregates accumulate as flies age until cell death is detected in vivo.•A critical threshold of aggregated polyQ proteins is associated to degeneration.•Three models of polyglutamine diseases lead to similar results.